A Strategy for the Periodic Assessment of the Degree of Hypertension Control in the Community - Birkett, John Nicholas (My University, 1978)
Hypertension is a chronic affliction which has a significant economic and health impact on Canadian society. Efforts to control hypertension are likely to produce significant returns, if the programs are effective in treating the hypertensive population. Before research efforts can be profitably directed at determining the most efficient method of achieving hypertension control, the state of, and deficiences in, the present health care system must be identified. The best approach to obtaining the information needed to evaluate the present system, is through a special-purpose, population-based survey.
The proper methodologic design of a population survey requires the use of probability sampling procedures. In addition, the blood pressure should be measured at several visits, using a standardized procedure. Examination of the literature reveals that no study satisfies all of the basic standards.
It is possible to identify six steps that must be followed if hypertension control is to be achieved. These steps form a conceptual model that can provide the basis of a general measurement strategy that can be used to assess the degree of hypertension control in a specific community.
This measurement strategy is used to develop a survey design to measure the degree of hypertension control in the Province of Ontario. A specially-created interview team will examine 3,850 individuals, located in selected geographic areas across the Province. Blood pressure will be measured using a Hawksley Random-zero Sphygmomanometer, at a maximum of three separate visits. Questionnaires will be developed to obtain valid information about health knowledge, attitudes and beliefs. The survey design will permit regional comparisons.
Keywords: Medical Sciences; Medical Sciences